PENERAPAN ALGORITMA NAÃVE BAYES DALAM PERANCANGAN SISTEM INFORMASI GROUND REFUELLING PESAWAT BERBASIS WEB DI BANDAR UDARA HUSEIN SASTRANEGARA BANDUNG - Cynthia Rahmawati; Betesda Betesda (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2024)
Based on previous observations by researchers, it was determined that there is a possibility of dishonesty/discrepancy between the number of refuelings and the quantity ordered. Therefore, it was necessary to carry out a system development cycle, commonly called SDLC (System Development Lyfe Cycle) in the digital form process. The results of the research show that the application of the NaÃ¯ve Bayes Algorithm calculation obtained a Prior Probability result in a probability of success or P (success) of 6/10. Meanwhile, the likelihood probability value by taking into account the weather variable produces a high probability value when it is sunny on failure and rain on failure has the same value of Â½, if done manually. Therefore, it is necessary to design a web-based system as a basis for the effectiveness of the ground refueling process and preventing data discrepancies, as well as storing documents or files properly. It is important to implement this digitalization into an airport's system, especially with regard to aircraft refueling at the airport, so that it facilitates the process of aircraft refueling and archiving data collection and the data obtained is more accurate.